Miscellania dentata gen. et sp.n. (Polychaeta: Syllidae) from the Spanish Mediterranean coast - Martin, Daniel; Alós, Carmen; Sardá, Rafael (Zoologica Scripta, 1990)
Specimens of Miscellania dentata gen. et sp.n. were collected in Catalunya, the Balearic Islands, and Strait of Gibraltar. They are characterized by an anterior tooth and an incomplete crown of denticles on the tip of the pharynx, short and smooth antennae and cirri, bases of palps separated, and the presence of compound and simple setae. Specimens were found living inside calcareous algal concretions.
World Polychaeta Database (WPolyDb)